The A list : [large type] an Ali Reynolds mystery - Jance, Judith A. (Jance, Judith A. Ali Reynolds mysteries., 2019)
The death of an old friend brings Ali back to the last story she ever reported: a feel-good human interest piece about a young man in need of a kidney to save his life, which quickly spiraled into a medical mismanagement scandal that landed a prestigious local doctor in prison for murder. Years may have passed, but Dr. Edward Gilchrist has not forgotten those responsible for his downfall -- certainly not Ali Reynolds, who exposed his dirty deeds to the world. Life without parole won't stop him from getting his revenge. Tattooed on his arm are the initials of those who put him behind bars, and he won't stop until every person on that Annihilation List is dead.